How Machismo Got Its Spurs—in English: Social Science, Cold War Imperialism, and the Ethnicization of Hypermasculinity - Benjamin Arthur Cowan (Latin American Research Review, 2017)
This article seeks to shift the framework of decades-long debates on the nature and significance of 'machismo', debunking the commonly held notion that the word describes a primordial Iberian and Ibero-American phenomenon. I trace the emergence of machismo as an English-language term, arguing that a tradition of unself-consciously ethnocentric scholarship in the 1940s and 1950s enabled the word’s entrance, by the 1960s, into popular sources. In fact, 'machismo' was rather a neologism in Spanish, but midcentury US scholarship presumed the category’s empirical validity and applied to it to perceived problems in the “Latin” world. Much of 'machismo'’s linguistic purchase—the reason it has become a global shorthand for hypermasculinity—stemmed from mid to late twentieth-century anxieties about hemispheric security, the Cold War, immigration, and overpopulation, particularly vis-à-vis the United States’ near neighbors, Mexico and Puerto Rico. I have sought out the word’s earliest appearances in various English-language media (books, scholarly articles, newspapers, magazines, and television) and explained how it has long escaped scrutiny as a construct in and of itself. As a result, machismo has resisted the most earnest and well-intentioned of challenges to its scholarly primacy and remains a pathologizing point of departure in approaches to Latin American gender systems.